Facades of diversity - Leong, Susan; Kerr, Thor; Cox, Shaphan (2016)
This article focuses on urban space and heritage. Our aim is to understand how ordinary streets in Perth respond to urban change and how much these urban streets represent Western Australia’s heritage. The intention is to eschew the dominant branding of WA as Australia’s mining state and shift the spotlight so that in addition to the economic and material, light is also shed on the socio-cultural in the everyday and the vernacular. This project uses Henri Lefebvre’s rhythmanalysis approach to explore a contrapuntal reading of heritage that disrupts the deserving, dominant and fixed histories of High Road in Willetton and High Street in Fremantle. Amid the tides of migration, commerce, and cultures, heritage facades on High Street Fremantle appear singular and fixed, whereas multiple cultures have been extracted for sale on High Road. Superficially High Road seems diverse, but the overarching impulse across both sites is commerce – ‘Business as usual’ reigns.